Pelimpahan Kuota Jamaah Haji Yang Meninggal Kepada Ahli Waris - Kiking Mulyadi; Aden Rosadi; Usep Saepullah (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The performance of the Hajj pilgrimage is one of the pillars of Islam that must be fulfilled by Muslims who possess the ability (istita'ah). Due to the overwhelming number of applicants and the restrictions on the number of pilgrims allowed to depart each year imposed by the Saudi Arabian government, the Ministry of Religious Affairs of the Republic of Indonesia has limited the departure of prospective Hajj pilgrims through a quota system and the allocation of waiting numbers known as "nomor porsi" (quota numbers). One consequence of this situation is that some prospective Hajj pilgrims who have registered and received their quota numbers may pass away before their departure. To address this issue, the Director General of Hajj and Umrah Implementation has issued Decree Number 130 of 2020, which allows for the transfer of quota numbers to one of the heirs of a deceased prospective Hajj pilgrim who did not have the opportunity to perform the pilgrimage. The findings of the study indicate that the Hajj quota of a deceased prospective pilgrim is part of their rights that fall into the category of inheritance. When such a right falls into this category, it can become an inheritance that must be divided among heirs who meet the requirements.